WAYS TO INTEGRATE EUROPEAN MASSIVE OPEN ONLINE COURSES IN UKRAINE’S UNIVERSITY EDUCATION - Bacurovska, Ilona (Educological discourse, 2017)
Educational online courses are gaining increasing popularity. Education is one of the few areas where age and preservation of traditions are benefits. Unlike the modern offline education, this study is caused by personal motivation and desire to gain the necessary knowledge. In world practice, a concept of massive open online courses appeared long time ago. The paper provides an analytical review of ways of implementing European massive open online courses in university education of Ukraine and their capabilities. Higher education needs urgent restructuring. Massive open online courses can help students combine their acquisition effectiveness and ease of scalability.